2011
DOI: 10.1183/09031936.00162009
|View full text |Cite
|
Sign up to set email alerts
|

A prospective polysomnographic study on the evolution of complex sleep apnoea

Abstract: Complex sleep apnoea (CompSA) may be observed following continuous positive airway pressure (CPAP) treatment.In a prospective study, 675 obstructive sleep apnoea patients (mean age 55.9 yrs; 13.9% female) participated. Full-night polysomnography was performed at diagnosis, during the first night with stable CPAP and after 3 months of CPAP.12.2% (82 out of 675 patients) had initial CompSA. 28 of those were lost to follow-up. Only 14 out of the remaining 54 patients continued to satisfy criteria for CompSA at fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 32 publications
7
61
0
4
Order By: Relevance
“…Cassel et al in their study, also observed a higher male to female ratio of 7:1. 6,7 Male preponderance was also observed in present study with male to female ratio of 3.2:1. Most patients with severe OSA were males (94.7%) and in females mild and moderate OSA were common (66.7%).…”
Section: Discussionsupporting
confidence: 63%
“…Cassel et al in their study, also observed a higher male to female ratio of 7:1. 6,7 Male preponderance was also observed in present study with male to female ratio of 3.2:1. Most patients with severe OSA were males (94.7%) and in females mild and moderate OSA were common (66.7%).…”
Section: Discussionsupporting
confidence: 63%
“…However, CPAP seems to be effective in some patients, while ineffective in others; CompSAS may develop de novo in 4% of OSAS patients treated with CPAP during follow up (17). Very few data are available on CPAP compliance, but there are suggestions that CompSAS patients may have a lower effect of CPAP on sleep as well as on breathing parameters, more dyspnea, poorer CPAP adherence and more often report spontaneous removal of the mask at night (18).…”
Section: Editorialmentioning
confidence: 98%
“…It is characterized by recurrent episodes of partial (hypopnea) or complete (apnea), obstruction of the upper airway during sleep, and it is associated with episodes of arousal and/or oxyhemoglobin desaturation. 2 Symptoms of the syndrome are reported in Table 1. The pathophysiology of obstructive sleep apnea is still controversial.…”
Section: Specific Conditions For Non-invasive Ventilation Obstructivementioning
confidence: 99%
“…Agata Lax, 1 Simona Colamartino, 2 Paolo Banfi, 1 Antonello Nicolini 2 N o n -c o m m e r c i a l u s e o n l y of the pharynx (see genioglossus) should produce a greater contraction to overcome the tendency of the pharyngeal wall to collapse (due to the negative pressure inside the cavity and pharynx). The supine position is dangerous obstruction as the tongue tends and occludes the rear wall of the oropharynx.…”
Section: Sleep-related Breathing Disorders and Non-invasive Ventilationmentioning
confidence: 99%